The Impact of Green Revolution Implementation on Rice Crop Productivity in Ngawi Regency During the New Order Era - Abdul Fikar Khajar; Shokheh, Mukhamad (Program Studi Pendidikan Sejarah - Universitas Samudra, 2026)
The Green Revolution is a concept of modern input-based agriculture adopted by Indonesia during the New Order era to increase and accelerate production in the agricultural sector. This study aims to chronologically describe the implementation process of the agricultural intensification program and its correlation with the dynamics of rice productivity in Ngawi Regency during the New Order period. In line with national objectives, this intensification was intended to increase food crop production amidst growing population numbers. The intensification project was carried out by referring to five main efforts, including: the use of selected seed varieties, pest control using pesticides, the use of chemical-based fertilizers, the development of irrigation infrastructure, and land management improvements. This study uses an empirical analysis method based on two main sources: annual BPS (Central Statistics Agency) report data and references from scientific works related to the implementation of the Green Revolution in Indonesia. The study's conclusion confirms that the application of modern inputs resulted in fluctuations in rice production in Ngawi Regency. These findings fill a gap in the scientific literature that has not yet addressed the specific historical aspects of the Ngawi case. In this study, it is universally acknowledged that modern inputs successfully increased rice agricultural yields in Ngawi; however, based on several recent research findings, the Green Revolution has significantly contributed to the emergence of future ecological problems. Therefore, to present an accurate historical narrative, this study implicitly recommends that further in-depth research be conducted to enrich agricultural knowledge, particularly in Ngawi. Keywords: Green Revolution, paddy crop productivity, Ngawi Regency